178. Vaccine Effectiveness Against Influenza-associated Hospitalizations and Emergency Department (ED) Visits Among Children in the United States in the 2019–2020 Season. (31st December 2020) - Campbell, Angela P; Ogokeh, Constance E; Weinberg, Geoffrey A; Boom, Julie A; Englund, Janet A; Williams, John V; Halasa, Natasha B; Selvarangan, Rangaraj; Staat, Mary A; Klein, Eileen J; McNeal, Monica; Michaels, Marian G; et al.
Abstract: Background: The 2019–20 influenza season was predominated by early onset B/Victoria viruses followed by A(H1N1)pdm09 virus circulation. Over 95% of circulating B/Victoria viruses were subclade V1A.3, different from the Northern Hemisphere vaccine strain. Annual estimates of influenza vaccine effectiveness (VE) are important because of frequent changes in circulating and vaccine viruses. Methods: We assessed VE among children 6 months–17 years old with acute respiratory illness and < 10 days of symptoms enrolled during the 2019–20 influenza season at 7 pediatric hospitals (ED patients < 5 years at 3 sites) in the New Vaccine Surveillance Network. Combined mid-turbinate/throat swabs were tested for influenza virus using molecular assays. We estimated age-stratified VE from a test-negative design using logistic regression to compare odds of vaccination among children testing positive versus negative for influenza, adjusting for age in years, enrollment month, and site. For these preliminary analyses, vaccination status was by parental report. Results: Among 2022 inpatients, 324 (16%) were influenza positive: 38% with influenza B/Victoria alone and 44% with influenza A(H1N1)pdm09 alone (Table). Among 2066 ED children, 653 (32%) were influenza positive: 45% with influenza B/Victoria alone and 43% with influenza A(H1N1)pdm09 alone. VE was 62% (95% confidence interval [CI], 51%–70%) against any influenza-related hospitalizations, 68% (95% CI, 55%–78%) for A(H1N1)pdm09 and 55% (95% CI, 35%–69%) for B/Victoria. VE by age group for any influenza-related hospitalizations was 57% (95% CI, 40%–69%) among children 6 months to < 5 years and 66% (95% CI, 49%–77%) among children 5–17 years. VE was 53% (95% CI, 42%–62%) against any influenza-related ED visits, 46% (95% CI, 28%–60%) for A(H1N1)pdm09 and 54% (95% CI, 39%–66%) for B/Victoria. VE by age group was 52% (95% CI, 37%–63%) among children 6 months to < 5 years and 42% (95% CI, 16%–60%) among children 5–17 years. Conclusion: Influenza vaccination in the 2019–20 season provided substantial protection against laboratory-confirmed influenza-associated hospitalizations and ED visits associated with the two predominantly circulating influenza viruses among children, including against the emerging B/Victoria virus V1A.3 subclade. Disclosures: Janet A. Englund, MD, AstraZeneca (Scientific Research Study Investigator)GSK group of companies (Scientific Research Study Investigator)Meissa vaccines (Consultant)Merck (Scientific Research Study Investigator)Sanofi Pasteur (Consultant) John V. Williams, MD, GlaxoSmithKline (Advisor or Review Panel member)IDConnect (Advisor or Review Panel member)Quidel (Advisor or Review Panel member) Natasha B. Halasa, MD, MPH, Genentech (Other Financial or Material Support, I receive an honorarium for lectures - it's a education grant, supported by genetech)Karius (Consultant)Moderna (Consultant)Quidel (Grant/Research Support, Research Grant or Support)Sanofi (Grant/Research Support, Research Grant or Support) Christopher J. Harrison, MD, GSK (Grant/Research Support, Infant menigiciccal B conjugate vaccine trial)Merck (Research Grant or Support, Infant pneumococcal conjugate vaccine trial)